2003
DOI: 10.1051/vetres:2003030
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis of dairy small ruminants

Abstract: -Staphylococci are the main aetiological agents of small ruminants intramammary infections (IMI), the more frequent isolates being S. aureus in clinical cases and coagulase negative species in subclinical IMI. The clinical IMI, whose annual incidence is usually lower than 5%, mainly occur at the beginning of machine milking and during the first third of lactation. These features constitute small ruminant peculiarities compared to dairy cattle. Small ruminant mastitis is generally a chronic and contagious infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
381
4
28

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(470 citation statements)
references
References 95 publications
38
381
4
28
Order By: Relevance
“…However, Hogan et al [23] did not find any effect under field conditions and did not support the hypothesis. There are marked differences between cows and ewes: M. haemolytica is a common mastitis agent in sheep, whilst Escherichia coli or Streptococcus uberis are not; ewes suckle their lambs for a period of up to three months, subsequently being hand-milked [3,4]. Therefore, findings from one species should not be directly extrapolated for the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Hogan et al [23] did not find any effect under field conditions and did not support the hypothesis. There are marked differences between cows and ewes: M. haemolytica is a common mastitis agent in sheep, whilst Escherichia coli or Streptococcus uberis are not; ewes suckle their lambs for a period of up to three months, subsequently being hand-milked [3,4]. Therefore, findings from one species should not be directly extrapolated for the other.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we inoculated bacteriologically positive teats with a M. haemolytica isolate, in order to study possible interactions between the bacterial flora and a confirmed mastitis causal agent [3,4]. Ewes in subgroup A1 and D developed subclinical mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently isolated pathogens in mastitis of ruminants are staphylococci, and S. aureus is considered a major pathogen responsible for considerable increases in milk leucocyte concentration and clinical mastitis [2,4,18]. Since phagocytosis by neutrophils is an important defense of the mammary gland of ruminants against mastitis-causing bacteria [12,17], the production of leucotoxins may confer on S. aureus an increased capacity to resist host defenses and to settle in the mammary gland.…”
Section: Introductionmentioning
confidence: 99%
“…Ovine mastitis is a widespread disease of ewes with significant adverse production effects [7,8]. The disease has not been studied as extensively as that in cows; consequently mechanisms of its pathogenesis have not been clarified and accurate control measures have not been proposed.…”
Section: Introductionmentioning
confidence: 99%